Edge computing in IoT-enabled honeybee monitoring for the detection of "Varroa destructor" - Wachowicz, Anna; Pytlik, Jakub; Małysiak-Mrozek, Bożena; Tokarz, Krzysztof; Mrozek, Dariusz (Zielona Góra: Uniwersytet Zielonogórski)
Among many important functions, bees play a key role in food production. Unfortunately, worldwide bee populations have been decreasing since 2007. One reason for the decrease of adult worker bees is varroosis, a parasitic disease caused by the "Varroa destructor" ("V. destructor") mite. Varroosis can be quickly eliminated from beehives once detected. However, this requires them to be monitored continuously during periods of bee activity to ensure that "V. destructor" mites are detected before they spread and infest the entire beehive. To this end, the use of Internet of things (IoT) devices can significantly increase detection speed.
Keywords: Internet of Things (IoT); Varroa destructor; precision beekeeping; machine learning; cloud; image processing; edge devices